2003
DOI: 10.1007/s00415-003-0971-x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin A reduces neurogenic flare but has almost no effect on pain and hyperalgesia in human skin

Abstract: Botulinum toxin A (BoNT/A) has been used therapeutically to treat muscular hypercontractions and sudomotor hyperactivity. There is increasing evidence that BoNT/A might also have analgesic properties, in particular in headache. In the present investigation we tested the often cited hypothesis that BoNT/A-induced analgesia can be attributed to inhibition of neuropeptide release from nociceptive nerve fibers. In 15 healthy volunteers BoNT/A (5, 10, 20 mouse units BOTOX) or saline (contralateral side) was injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 46 publications
7
65
1
7
Order By: Relevance
“…In contrast, the flare response/increase in CBF produced by capsaicin was inhibited by BoNT/A either if capsaicin was applied to the same area or in an area adjacent to that treated with BoNT/A. Present data confirm, in part, a previous study which shows that pretreatment with BoNT/A reduced the flare response by painful transcutaneous electrical stimulation (Kramer et al, 2003). However, the reduction in vasodilatation observed in BoNT/A treated side does not seem to contribute significantly to capsaicin-induced pain.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast, the flare response/increase in CBF produced by capsaicin was inhibited by BoNT/A either if capsaicin was applied to the same area or in an area adjacent to that treated with BoNT/A. Present data confirm, in part, a previous study which shows that pretreatment with BoNT/A reduced the flare response by painful transcutaneous electrical stimulation (Kramer et al, 2003). However, the reduction in vasodilatation observed in BoNT/A treated side does not seem to contribute significantly to capsaicin-induced pain.…”
Section: Discussionsupporting
confidence: 79%
“…In particular, results obtained from the measurement of thermal and electric pain thresholds, acute pain perception, hyperalgesia and flare in response to capsaicin application to the human skin seemed to rule out a direct analgesic effect of BoNT/A (Voller et al, 2003). However, findings obtained in facial pain (Borodic et al, 2001;Borodic and Acquadro, 2002) and in a rat model of inflammatory pain (Cui et al, 2002;Aoki, 2003;Cui et al, 2004) and in humans by transcutaneous electrical stimulation (Kramer et al, 2003) focused on the possibility that BoNT/A somehow limits the functioning of a subset of capsaicin-sensitive and neuropeptide-containing primary sensory neurons (Durham et al, 2004).…”
Section: Introductionmentioning
confidence: 89%
“…Based on this observation the authors proposed that the toxin's antiinflammatory effect on neurogenic flare and vasodilatation do not significantly contribute to BoNT/A-mediated pain reduction (Tugnoli et al, 2007). Similar conclusion was proposed in the human study of Krämer et al (2003) which reported that BoNT/A reduced neurogenic flare evoked by cutaneous electrical stimulation, however, with very limited analgesic effect.…”
Section: Dissociation Of Bont/a Antinociceptive Activity and Periphsupporting
confidence: 57%
“…The authors suggested that the neuropeptide-mediated reduction of peripheral neurogenic inflammation does not contribute significantly to BoNT/A analgesic effects observed in clinical pain syndromes (Krämer et al, 2003).…”
Section: Dissociation Of Bont/a Antinociceptive Activity and Periphmentioning
confidence: 99%
“…The promising experience of Swartling and Vahlquist led the same authors to an interesting retrospective evaluation of the effects of BoNT-A injections in 14 patients with EBS and PC with foot blisters and painful callosities [47] . They observed analogues results in improvement of blisters and pain; the hypothesis that explains these effects was that BoNT-A can affects nociceptive C-fibers in the skin via inhibition of neuropeptide release from sensory nerve axons and also inhibits the neurogenic inflammation [48] . Recently, 2 new cases of PC treated with BoNT-A injection have been described [49] .…”
Section: Pachyonychia Congenitamentioning
confidence: 99%